2006
DOI: 10.1073/pnas.0511299103
|View full text |Cite
|
Sign up to set email alerts
|

Wnt signaling in the thymus is regulated by differential expression of intracellular signaling molecules

Abstract: Wnt signaling is essential for T cell development in the thymus, but the stages in which it occurs and the molecular mechanisms underlying Wnt responsiveness have remained elusive. Here we examined Wnt signaling activity in both human and murine thymocyte populations by determining ␤-catenin levels, Tcf-reporter activation and expression of Wnt-target genes. We demonstrate that Wnt signaling occurs in all thymocyte subsets, including the more mature populations, but most prominently in the double negative (DN)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
124
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(138 citation statements)
references
References 29 publications
9
124
0
4
Order By: Relevance
“…Reports based on in vivo assessment of TCF reporter activity or b-catenin transgenic expression in developing thymocytes have provided evidence that, during intrathymic development, Wnt signaling follows a biphasic dynamics with peak levels corresponding to pre-and post-b-selection cell proliferation. Consistent with this view, Wnt signaling reaches maximum levels in DN1 and DN2 thymocytes (23), ceases in DN3 thymocytes (17), re-increases in pre-TCR expressing thymocytes, and ends in post-b-selection CD4 + CD8 + early DP thymocytes (43,44). Thus, during Tab lymphocyte development, cessation of Wnt signaling coincides with the two successive phases of TCR rearrangement.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Reports based on in vivo assessment of TCF reporter activity or b-catenin transgenic expression in developing thymocytes have provided evidence that, during intrathymic development, Wnt signaling follows a biphasic dynamics with peak levels corresponding to pre-and post-b-selection cell proliferation. Consistent with this view, Wnt signaling reaches maximum levels in DN1 and DN2 thymocytes (23), ceases in DN3 thymocytes (17), re-increases in pre-TCR expressing thymocytes, and ends in post-b-selection CD4 + CD8 + early DP thymocytes (43,44). Thus, during Tab lymphocyte development, cessation of Wnt signaling coincides with the two successive phases of TCR rearrangement.…”
Section: Discussionsupporting
confidence: 60%
“…The role of the b-catenin coactivator in thymocyte proliferation and differentiation is more controversial. Although it has been shown that immature thymocytes display intranuclear b-catenin (23) and that b-catenin conditional stabilization allows thymocytes to bypass the requirement for pre-TCR signaling to reach the DP stage, neither b-catenin ablation nor b-and g-catenin combined absence affects intrathymic development (18,19). One possible explanation is that a still undefined alternate b-catenin-independent noncanonical pathway regulates intrathymic LEF1/TCF7 activity.…”
Section: Discussionmentioning
confidence: 92%
“…[79][80][81][82] Conversely, Fz receptors are expressed primarily by the thymocytes, but also by stromal cells. 79 79 Recently, our group has shown that mainly DN1-3 thymocytes undergo Wnt signaling.…”
Section: Notch and Wnt Signaling In T-cell Development And T-allmentioning
confidence: 99%
“…79 79 Recently, our group has shown that mainly DN1-3 thymocytes undergo Wnt signaling. 82 Retroviral transduction of fetal thymocytes with Wnt1 and Wnt4 increased their proliferation in culture. 79 Furthermore, blocking Wnt binding using soluble Fz receptors completely inhibited T-cell development at the DN and ISP stages.…”
Section: Notch and Wnt Signaling In T-cell Development And T-allmentioning
confidence: 99%
“…One of the proteomic methodologies that is suitable for proteome profiling is capillary electrophoresis coupled to mass spectrometry (CE-MS). 3 Advantages of CE-MS include automation, high-throughput capability, high sensitivity, and less demand of sample volume.…”
Section: ------------------------------------------------------------mentioning
confidence: 99%